Additional of Organic Amendments in the Soil to Increase the Various Crop Yield: A Review - Norsuhailizah, Sazali; Zawati, Harun; Norazlianie, Sazali (Semarak Ilmu Publishing, 2024)
Agricultural production is threatened by the scarcity of current natural resources, an increasing total population, climatic change, and degraded soils. To feed the world's growing population, development strategies must be implemented that sustainably increase agricultural production while at the same time reducing the negative impacts of the activities. A number of amendments are currently being researched to improve the structure and fertility of soils. The properties of organic materials (biochar (BC), husk, and compost) were examined. The properties of BC have a large specific surface area, are highly porous, and have a high cation exchange capacity (CEC). These amendments could be used to slow down the continuous soil degradation and maintain soil productivity while facing global challenges. While the environmental effects have been extensively studied, the extent to which they can contribute to long-term intensification has yet to be determined. This review aims to contribute to the topic by providing a concise summary that combines both environmental evidence and agronomic considerations.